Manganese transport is essential for N2‐fixation by Rhizobium leguminosarum in bacteroids from galegoid but not phaseoloid nodules - Hood, G; Ramachandran, V; East, A; Downie, J; Poole, P (Wiley, 2017)
Rhizobium leguminosarum has two high‐affinity Mn2+ transport systems encoded by sitABCD and mntH. In symbiosis, sitABCD and mntH were expressed throughout nodules and also strongly induced in Mn2+‐limited cultures of free‐living cells. Growth of a sitA mntH double mutant was severely reduced under Mn2+ limitation and sitA and mntH single mutants were more sensitive to oxidative stress. The double sitA mntH mutant of R. leguminosarum was unable to fix nitrogen (Fix‐) with legumes belonging to the galegoid clade (Pisum sativum, Vicia faba and Vicia hirsuta). The presence of infection thread‐like structures and sparsely‐packed plant cells in nodules suggest that bacteroid development was blocked, either at a late stage of infection thread progression or during bacteroid‐release. In contrast, a double sitA mntH mutant was Fix+ on common bean (Phaseoli vulgaris), a member of the phaseoloid clade of legumes, indicating a host‐specific symbiotic requirement for Mn2+ transport.